2018
DOI: 10.1111/cid.12647
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin C in wound healing after dental implant surgery in patients treated with bone grafts and patients with chronic periodontitis

Abstract: Using vitamin C supplementation improves postoperative healing following dental implant surgery in patients with chronic periodontitis and patients treated with GBR or Bio-Oss Collagen grafts. However, vitamin C supplementation does not decrease the postoperative pain associated with dental implant surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 44 publications
0
28
1
4
Order By: Relevance
“…AA is an effective antioxidant that relieves oxidative stress and participates in a variety of biochemical reactions. Moreover, AA is able to decrease the responses of some inflammatory biomarkers and several pro-inflammatory cytokines [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…AA is an effective antioxidant that relieves oxidative stress and participates in a variety of biochemical reactions. Moreover, AA is able to decrease the responses of some inflammatory biomarkers and several pro-inflammatory cytokines [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This micronutrient plays an important role in the biosynthesis of collagen, which is an important component of connective tissue of the gingiva, peri-implant mucosa, and alveolar bone [58]. These effects were confirmed by Li et al [47], who found that vitamin C supplementation improved postoperative wound healing following dental implant surgery. Moreover, protective effects of this intervention on bone health could be expected, as vitamin C could hinder the effects of oxidative stress in promoting bone resorption and consequently reducing bone strength [59], although this hypothesis is not yet confirmed.…”
Section: Discussionmentioning
confidence: 79%
“…Li et al, in 2018 [47], evaluated the effects of vitamin C supplementation on four populations: patients receiving dental implants by guided bone regeneration (GBR), patients treated with Bio-Oss collagen, patients with chronic periodontitis receiving dental implants, and a control group without any bone grafting or periodontal disease. The authors found that vitamin C supplementation improved postoperative wound healing following dental implant surgery in patients with chronic periodontitis and in those treated with GBR or Bio-Oss collagen grafts.…”
Section: Vitamin Cmentioning
confidence: 99%
“…Застосування добавок вітаміну С сприяло покращенню загоєння рани після встановлення дентальних імплантатів у пацієнтів з одномоментно проведеною аугментацією та у пацієнтів із наявною патологією пародонта, проте ніяк не впливало на вираження больового симптому в післяопераційний період [22]. У групі пацієнтів, яким не проводилось суміжної аугментації, та в яких не було зареєстровано ознак пародонтиту, додаткове споживання вітаміну С не сприяло оптимізації процесу загоєння рани [22].…”
Section: потенційний вплив особливостей дієти на процес остеоінтеграції дентальних імплантатівunclassified